2021
DOI: 10.1155/2021/6630598
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Strategy for Patients with Tourette Syndrome Based on Clinical Efficacy and Safety: A Meta-Analysis of 47 Randomized Controlled Trials

Abstract: Objective. Although increasing evidence reveals the efficacy of traditional Chinese medicine (TCM) and its safety on Tourette Syndrome (TS) patients, whether TCM is indeed improving TS remains unclear. The purpose of the current study is to perform a meta-analysis to evaluate the efficacy and safety of TCM on treating TS patients. Method. An elaborate search strategy was conducted based on several databases including Medline, Embase, Cochrane, Web of Science, CINAHL, CBM, VIP, CNKI, and Wanfang Data in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…However, the evidence regarding TCM's effectiveness and safety in the treatment of TS is conflicting. For example, in their meta-analysis, Wang et al [20] studied 47 randomized controlled trials from 2004 to 2014 and recommended TCM to treat TS patients with better efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence regarding TCM's effectiveness and safety in the treatment of TS is conflicting. For example, in their meta-analysis, Wang et al [20] studied 47 randomized controlled trials from 2004 to 2014 and recommended TCM to treat TS patients with better efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative therapies like Chinese traditional medicine (CTM) are shown to have some benefit for the treatment of TS although their efficacy is still up for debate. A metanalysis of the 26 trials that utilized YGTSS to assess tic severity found that those who used CTM showed significant improvement in YGTSS-TTS compared to those in the control groups (SMD = −0:21, 95% CI: −0.29 to −0.14, I2 = 12:30%) [ 63 ]. The 5-ling granule (5-LGr) and Ningdong granule are common CTM used to treat TS in China.…”
Section: Epidemiologymentioning
confidence: 99%
“…A meta-analysis of 47 randomized controlled trials [65] showed that Changma Xifeng tablets and Jiuwei Xifeng granules had obvious clinical efficacy in the treatment of TS, but their specific therapeutic effects need more scientific verification.…”
Section: Traditional Chinese Medicine Treatment Of Tsmentioning
confidence: 99%